Incidence of venous thromboembolism after surgery for adenocarcinoma in situ and the validity of the modified Caprini score: A propensity score-matched study - Cai, Yong-sheng; Dong, Hong-hong; Li, Xin-yang; Ye, Xin; Chen, Shuo; Hu, Bin; Li, Hui; Miao, Jin-bai; Chen, Qi-rui (Frontiers in Oncology, 2022)
Background:Recently, the new World Health Organization (WHO) tumor classification removed adenocarcinoma in situ (AIS) from the diagnosis of lung cancer. However, it remains unclear whether the "malignancy" item should be assessed when the modified Caprini Risk Assessment Model (RAM) is used to assess venous thromboembolism (VTE) risk in AIS. The purpose of our study is to assess differences between AIS and stage IA adenocarcinoma (AD) from a VTE perspective. Methods:A retrospective study was performed on AIS and IA adenocarcinoma in our hospital from January 2018 to December 2021, and divided into AIS group and AD group. Propensity score matching (PSM) was used to compare the incidence of VTE and coagulation function, and to analyze whether the RAM is more effective when the "malignancy" item is not evaluated in AIS. Results: 491 patients were included after screening, including 104 patients in the AIS group and 387 patients in the AD group. After PSM, 83 patients were matched. The incidence of VTE and D-dimer in the AIS group was significantly lower than that in the AD group (P<0.05).When using the RAM to score AIS, compared with retaining the "malignancy" item, the incidence of VTE in the intermediate-high-risk group was significantly higher after removing the item (7.9% vs. 36.4%, P=0.018), which significantly improved the stratification effect of the model. Conclusions:The incidence of postoperative VTE in AIS was significantly lower than that in stage IA adenocarcinoma. The stratification effect was more favorable when the "malignancy" item was not evaluated in AIS using the RAM.